Study of Multiple Genotypes in the XPD gene for A/C Lys751Gln and Lung Cancer in Samples from Baghdad–Iraq (Medico Legal Update, 2021)
The chance of treating lung cancer is very low due to late diagnosis of metastasis. Therefore, the study of lungcancer and its related genetic patterns is of great importance in early diagnosis of infected individuals. Thisstudy analyzes the replication of A/C Lys751Gln polymorphisms of the XPD gene in the Iraqi populationand the risk of its association with lung cancer. The results suggest that the heterozygous genotype Lys/Gln increases the risk of lung cancer, while Lys/Lys reduces at least the risk of lung cancer, WhileGln/Glngenotype does not show any significant increase in the risk of lung cancer. These types of studies helpexperts in timely diagnosis and use of effective remedial procedures especially in individuals who havepatients from family members, relatives and couples in the case of endogamy . We hope that the associationbetween these forms and lung cancer will be more clearly determined with statistical analyses in differentpopulations as well as we suggest using this technique as a diagnostic biomarker in lung cancer patients.This study aimed to assess the effect of polymorphism on genotypes in the XPD gene on the susceptibilityof lung cancer in Iraqi patients.